Dinamika Otonomi Daerah dan Demokrasi Lokal di Provinsi Sumatera Selatan - Rama Islamiyana; Tengku Rika Valentina; Ira Wati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
Expansion of a region within a province is a political condition to provide regional autonomy that prioritizes regional progress in a smaller scope in order to maximize the results of the development of the region. Several phenomena occur in regional development studies. This study aims to analyze the dynamics that occur in regional development based on the concept of regional autonomy. The object chosen in this study is the province of South Sumatra. The selection of South Sumatra as the object of this research is based on the area size and equity that has not been maximized in this province. This study found that regional expansion is a form of necessity to maximize social welfare, political participation and political stability that occurs in an area. Political and government regulations in a smaller scope are able to maximize regional capacity to optimize people's welfare. However, in other findings, regional expansion has an unavoidable clash. The interest of political elites in the process of regional expansion is one of the problems that continues to occur. This study uses an exploratory-qualitative research design method with the concept of decentralization and regional autonomy and local democracy as an analytical tool in the discussion.